Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea - Korshunova, T.; Martynov, A.; Picton, B. (Zootaxa, 2017)
The taxonomy of aeolidacean nudibranchs of the traditional group previously known as Tergipedidae is discussed. To integrate the diverse molecular phylogenetic pattern and morphological disparity in a broadly ontogenetic context a revised classification at the family level is presented. The families Calmidae Iredale & O'Donoghue, 1923, Eubranchidae Odhner, 1934, Fionidae Gray, 1857 s. str. (restricted, with the genus Fiona only), and Tergipedidae Bergh, 1889 s.str. (restricted, with inclusion of the genus Tergipes only) are restored. The families Cuthonidae Odhner, 1934 s.str. (restricted, with only single genus Cuthona), Cuthonellidae Miller, 1971, stat. nov., and Trinchesiidae Nordsieck, 1972 (with inclusion of the genera Catriona, Diaphoreolis, Phestilla, Tenellia, Trinchesia) are reinstated. At the genus level, the family Trinchesiidae appears as a most diverse assemblage that needs to be further divided. In the present study, the “Eolis” pustulata species complex is particularly investigated, including description of a new ontogenetically different species Zelentia ninel sp. nov. “Eolis” pustulata Alder & Hancock, 1854 and two closely related species are morphologically well separated from Trinchesia s. str. (absence of foot corners, narrow radular teeth) and form a distinct molecular phylogenetic clade basal to all the other Trinchesiidae. Therefore, this group is a distinct unit according to both morphological and molecular data and is separated here as a new genus, Zelentia gen. nov. The genus Catriona is also briefly discussed and the valid status of the species Catriona aurantia (Alder et Hancock, 1842) stat. nov. is confirmed.